Peran dunia usaha dan dunia industri dalam penyelenggaraan smk berbasis kearifan lokal di kota Mataram - Indriaturrahmi Indriaturrahmi; Sudiyatno Sudiyatno (Jurnal Pendidikan Vokasi, 2016)
Penelitian ini bertujuan untuk mengetahui: (1) peran DUDI dalam mendorong produk kebijakan pendidikan Pemda Kota Mataram dalam mengembangkan SMK berbasis kearifan lokal; (2) implementasi penyelenggaraan kebijakan pendidikan SMK yang sesuai dengan kearifan lokal; dan (3) peran DUDI dalam pengembangan SMK. Informan kunci pada penelitian adalah Kepala Dinas Dikmen sub-bagian kepala seksi kurikulum, Kepala Sekolah, Wakasek Humas Industri, Pembimbing Industri, dan Siswa. Teknik pengumpulan data melalui observasi, wawancara mendalam dan dokumentasi. Teknik analisis data meliputi reduksi data, penyajian data dan penarikan kesimpulan. Hasil penelitian ini menunjukkan bahwa: (1) peran DUDI dalam mendorong kebijakan Pemda terkait pengembangan SMK berbasis kearifan lokal belum memadai; (2) implementasi kebijakan Pemda, antara lain: (a) monitoring dan evaluasi, (b) menyediakan unit gedung baru, (c) membuka kompetensi keahlian baru, (d) pemberian dana, (e) mengadakan Gebyar SMK se-Kota Mataram; dan (3) peran DUDI dalam pengembangan SMK antara lain: (a) penyelenggaraan prakerin siswa berjalan dengan baik. b) industri sebagai tempat pemagangan guru, c) industri terlibat dalam uji kompetensi siswa tingkat akhir dan tempat menyalurkan lulusan, d) belum ada kerja sama terkait penyediaan sarana dan prasarana, dan e) pengembangan kurikulum dalam bentuk workshop kurikulum. Kata kunci: peran DUDI, penyelenggaraan SMK, kearifan lokal THE ROLE OF BUSINESS AND INDUSTRY IN THE IMPLEMENTATION OF VOCATIONAL HIGH SCHOOL (VHS) BASED ON LOCAL WISDOM IN THE CITY OF MATARAM Abstract This research aims to know: (1) the role of business and industry in encouraging the product education policy of the local government in Mataram City for developing vocaational high school (VHS) based on local wisdom; (2) the implementation of VHS education policy with an appropriate local wisdom; and (3) the role of business and industry in developing VHS. The key informants in this research were the Head of Secondary Education Curriculum Sub-section, Principal, Vice Principal of Industry Public Relations, Industry Counsellors, and students. The data were collected by observation, in-depth interviews and documentation. The data analysis technique included data reduction, data display and conclusion drawing. The results showed that: (1) the role of business and industry in encouraging the regional government policy related to VHS development based on local wisdom had not been adequate; (2) the implementation of regional government policy were among others: (a) monitoring and evaluation, (b) providing a new building unit, (c) opening new expertise competencies, (d) providing funds, (e) conducting Gebyar SMK in the city of Mataram; and (3) the roles of business and industry in the development of VHS were among others: (a) the implementation of the students' industrial practice ran well, (b) the industry as the place for teachers' apprenticeship, (c) the industry was involved in students' competency test at the end of the students' study and as an institute which would recruit the graduates, d) there had not been any cooperation related to the provision of facilities and infrastructure, and e) curriculum development in the form of a curriculum workshop. Keywords: the role of business and industry, implementation of VHS, local wisdom